2018
DOI: 10.1016/j.chom.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbes Egested during Bites of Infected Sand Flies Augment Severity of Leishmaniasis via Inflammasome-Derived IL-1β

Abstract: Leishmania donovani parasites are the cause of visceral leishmaniasis and are transmitted by bites from phlebotomine sand flies. A prominent feature of vector-transmitted Leishmania is the persistence of neutrophils at bite sites, where they protect captured parasites, leading to enhanced disease. Here, we demonstrate that gut microbes from the sand fly are egested into host skin alongside Leishmania parasites. The egested microbes trigger the inflammasome, leading to a rapid production of interleukin-1β (IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
161
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(181 citation statements)
references
References 38 publications
(63 reference statements)
8
161
0
3
Order By: Relevance
“…Neutrophils play important roles not only in the cutaneous forms but also in the experimental visceral form of the disease (Dey et al, 2018, McFarlane et al, 2008, Sacramento et al, 2015, Smelt et al, 2000. Decreased neutrophil recruitment in the liver and spleen of L. infantuminfected Tlr2 -/mice was recently described (Sacramento et al, 2017) further implying the importance of TLR2 signalling in the inflammatory response to infection with Leishmania spp inducing visceral diseases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Neutrophils play important roles not only in the cutaneous forms but also in the experimental visceral form of the disease (Dey et al, 2018, McFarlane et al, 2008, Sacramento et al, 2015, Smelt et al, 2000. Decreased neutrophil recruitment in the liver and spleen of L. infantuminfected Tlr2 -/mice was recently described (Sacramento et al, 2017) further implying the importance of TLR2 signalling in the inflammatory response to infection with Leishmania spp inducing visceral diseases.…”
Section: Discussionmentioning
confidence: 96%
“…Upregulation of KC mRNA and CXCL6 were previously shown to be associated with neutrophil recruitment following L. major infection (Muller et al, 2001, Uyttenhove et al, 2011. In addition to chemokines, other factors produced by the parasites (van Zandbergen et al, 2002) or contributed by the sand fly during natural infection such as egested bacteria, salivary gland products and a proteophosphoglycan gel, are likely to also participate in neutrophil recruitment (de Moura et al, 2010, Dey et al, 2018, Giraud et al, 2018. Thus, multiple factors may contribute and synergize to promote neutrophil recruitment at the site of infection.…”
Section: Discussionmentioning
confidence: 98%
“…24 Importantly, many independent groups have shown that several species of Leishmania, such as Leishmania amazonensis (L. amazonensis), Leishmania major (L. major), and Leishmania braziliensis (L. braziliensis), are able to induce NLRP3 inflammasome activation in bone marrow-derived macrophages (BMDMs), via both the canonic and noncanonic pathways. [25][26][27][28][29][30][31] However, robust IL-1 and CASP1 secretion can only be achieved with previous priming by TLRs agonists, such as LPS, 25,27,29,30 and the reasons for these particular requirements have never been addressed in the context of Leishmania infection.…”
Section: Introductionmentioning
confidence: 99%
“…An additional explanation for the large and sustained neutrophil infiltration at the bite sites was recently proposed and involves the immunomodulatory properties of gut microbes from infected sandflies that are co-egested with Leishmania parasites into the skin (Figure 1). Using a VL BALB/c mouse model intradermally infected in the ears by L. donovani, Dey et al demonstrated that the microbiota of the sandfly midgut enhances the early recruitment of neutrophils and the activation of the inflammasome in these cells, with the production of interleukin (IL)-1β, a potent proinflammatory cytokine [30]. These effects were abrogated with the pre-treatment of sandflies with antibiotic cocktails to decrease the microbial population prior to infection, or when mice were treated with an IL-1 receptor (IL1R) antagonist.…”
Section: Early Eventsmentioning
confidence: 99%
“…These effects were abrogated with the pre-treatment of sandflies with antibiotic cocktails to decrease the microbial population prior to infection, or when mice were treated with an IL-1 receptor (IL1R) antagonist. The authors concluded that the microbe-mediated IL-1β production serves as an autocrine signal that amplifies neutrophil infiltration at the infection sites and may also aid in parasite dissemination to the spleen [30]. Figure 1.…”
Section: Early Eventsmentioning
confidence: 99%